2015
DOI: 10.1159/000442029
|View full text |Cite
|
Sign up to set email alerts
|

Total Fluoride Intake by Children from a Tropical Brazilian City

Abstract: The main sources of fluoride intake by children are fluoridated water and toothpaste. Little has been studied regarding fluoride intake from these sources in regions with tropical climates and high temperatures throughout the year. This study aimed to determine the amount of fluoride ingested from diet and tooth brushing by children who live in a city with a tropical climate. Sixty-seven children from Teresina, Piauí, Brazil, took part in this study. The city's water supply was optimally fluoridated. The dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…This result is in disagreement with other studies conducted in Northeastern Brazil 8,10 as well as in other Brazilian regions, 6,18,19,23,24 where higher values were observed. In the present study, flavored toothpaste was the most frequently used and almost all children brushed at least twice a day, factors that have been cited in the literature as associated with the risk of fluorosis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This result is in disagreement with other studies conducted in Northeastern Brazil 8,10 as well as in other Brazilian regions, 6,18,19,23,24 where higher values were observed. In the present study, flavored toothpaste was the most frequently used and almost all children brushed at least twice a day, factors that have been cited in the literature as associated with the risk of fluorosis.…”
Section: Discussioncontrasting
confidence: 99%
“…al. 10 , who found that dentifrice was the largest source in a sample of the same city. A study is therefore needed to assess the total fluoride intake in children of low socioeconomic status, as they may be exposed to higher levels of fluoride.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations